A meta-analysis and systematic literature review of virtual reality rehabilitation programs. (May 2017) - Howard, Matt C.
Abstract: A recent advancement in the study of physical rehabilitation is the application of virtual reality rehabilitation (VRR) programs, in which patients perform practice behaviors while interacting with the computer-simulation of an environment that imitates a physical presence in real or imagined worlds. Despite enthusiasm, much remains unknown about VRR programs. Particularly, two important research questions have been left unanswered: Are VRR programs effective? And, if so, why are VRR programs effective? A meta-analysis is performed in the current article to determine the efficacy of VRR programs, in general, as well as their ability to develop four specific rehabilitation outcomes: motor control, balance, gait, and strength. A systematic literature review is also performed to determine the mechanisms that may cause VRR program success or failure. The results demonstrate that VRR programs are more effective than traditional rehabilitation programs for physical outcome development. Further, three mechanisms have been proposed to cause these improved outcomes: excitement, physical fidelity, and cognitive fidelity; however, empirical research has yet to show that these mechanisms actually prompt better rehabilitation outcomes. The implications of these results and possible avenues for future research and practice are discussed. Highlights: Virtual reality rehabilitation (VRR) programs are growing in popularity. VRR programs are more effective than traditional rehabilitation programs. Excitement, physical fidelity, and cognitive fidelity may cause VRR program success. More research is needed to better understand VRR programs.